Lower Vagal Response to the Cold Face Test during Acute Psychosocial Stress is Associated with Higher Cortisol Reactivity - Richer, Robert; Zenkner, Janis Joshua; Küderle, Arne; Rohleder, Nicolas; Eskofier, Björn (2024)
Background Stimulation of the parasympathetic nervous system (PNS) by the Cold Face Test (CFT) has the potential to successfully reduce biological responses to acute psychosocial stress in both the sympathetic nervous system (SNS) and the hypothalamic-pituitary-adrenal (HPA) axis. However, the link between PNS and HPA axis reactivity in an acute stress context has, to date, been underexplored. Methods We investigated the relationship between vagal function and HPA axis reactivity based on data from a study assessing the CFT as an intervention method for reducing acute psychosocial stress responses. In the intervention group, N=12 participants (92% women, 20.3 ± 2.8 years) were repeatedly exposed to the CFT during each phase of the Montreal Imaging Stress Task (MIST). Results We characterized the vagal response to the CFT as the CFT latency, defined as the duration between the beginning of the parasympathetic response to the CFT and peak bradycardia. Individuals who responded slower to the CFT showed a significantly higher AUCI (t = -2.66, p = 0.024, g = -1.42). In addition, CFT latency explained 63.4% of the maximum cortisol increase variance (F = 20.05, p = 0.001). Conclusion Despite the limited sample size, these initial results suggest a close relationship between vagal and HPA axis reactivity. It might lay the groundwork for future investigations that can employ the CFT as a potential index to examine the biopsychological stress reactivity of individuals and to better understand the underlying mechanisms to develop tailored interventions for better recovery from acute stress situation